Zakat, Infak, dan Sedekah terhadap Sustainable Development Goals (SDGs) di BAZNAS Kabupaten Demak (Institut Agama Islam Negeri Kudus, 2025)
Abstract Zakat, infak, and sedekah (ZIS) play a strategic role in supporting the Sustainable Development Goals (SDGs), particularly in alleviating poverty, reducing social inequality, empowering people economically, and enhancing community welfare. This study aims to analyze the influence of ZIS on the Sustainable Development Goals in BAZNAS Demak Regency for the 2019–2023 period, employing a descriptive quantitative approach. The research sample was taken using the Simple Random Sampling method, while the data were obtained through questionnaires, then processed and analyzed using multiple linear regression. Data quality testing was carried out through validity and reliability tests. Meanwhile, hypothesis testing used the t-test, F-test, and coefficient of determination. The results of the study indicate that ZIS has a significant effect on the achievement of Sustainable Development Goals at BAZNAS Demak Regency. Optimizing programs, such as capital assistance, skills training, and business mentoring, has been proven to increase the income of mustahik sustainably. These findings confirm that proper, innovative, and sustainable management of zakat, infak, and sedekah can make a real contribution to achieving sustainable development goals, especially in Demak Regency. Keywords: Zakat; Infak; Sedekah; Sustainable Development Goals (SDGs). Abstrak Zakat, infak, dan sedekah (ZIS) memiliki peran strategis dalam mendukung Sustainable Development Goals (SDGs), khususnya dalam pengentasan kemiskinan, pengurangan kesenjangan sosial, pemberdayaan ekonomi umat, serta peningkatan kesejahteraan masyarakat. Penelitian ini bertujuan menganalisis pengaruh ZIS terhadap Sustainable Development Goals di BAZNAS Kabupaten Demak periode 2019–2023 dengan pendekatan kuantitatif deskriptif. Sampel penelitian diambil menggunakan metode Simple Random Sampling, sedangkan data diperoleh melalui kuesioner, kemudian diproses, dan dianalisis menggunakan regresi linier berganda. Uji kualitas data dilakukan melalui uji validitas dan uji reliabilitas. Sementara uji hipotesis menggunakan uji t, uji F, dan koefisien determinasi. Hasil penelitian menunjukkan bahwa ZIS berpengaruh signifikan terhadap pencapaian Sustainable Development Goals di BAZNAS Kabupaten Demak. Optimalisasi program, seperti bantuan modal, pelatihan keterampilan, dan pendampingan usaha, terbukti mampu meningkatkan pendapatan mustahik secara berkelanjutan. Temuan ini menegaskan bahwa pengelolaan zakat, infak, dan sedekah yang tepat, inovatif, dan berkesinambungan dapat memberikan kontribusi nyata terhadap pencapaian tujuan pembangunan berkelanjutan, khususnya di Kabupaten Demak. Kata Kunci: Zakat; Infak; Sedekah; Sustainable Development Goals (SDGs).